2012
DOI: 10.1111/j.1756-1051.2012.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, salinity and cold stratification on seed germination in halophytes

Abstract: Salt tolerance of halophytes corresponds with the habitat requirement of the species. It is an important factor during the germination phase and it can determine successful establishment. This paper presents the effects of alternating temperaturelight regimes (4/8°C, 10/20°C, 20/32°C; 12 h dark: 12 h light) and different salinity levels (0, 200, 400, 600 mmol l 21 NaCl) on seed germination of five halophytes, Halimione pedunculata, Bupleurum tenuissimum, Aster tripolium, Triglochin maritimum and Armeria mariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In this report, we have used the halophytic Arabidopsis relative, E. salsugineum to identify biochemical alterations and dormancy-associated gene expression changes underlying the widespread phenomenon of salt-mediated inhibition of halophyte seed germination ( Ungar, 1978 ; Gulzar and Khan, 2001 ; Song et al, 2005 ; Qu et al, 2008 ; Orsini et al, 2010 ; Al-Hawija et al, 2012 ; Cao et al, 2012 ; Gul et al, 2013 ). It had been previously reported that E. salsugineum seed germination is inhibited by salt ( Inan et al, 2004 ; Orsini et al, 2010 ), and we further extended these findings to show that E. salsugineum seeds respond to as low as 50 mM NaCl, which causes a delay in germination ( Figure 1A ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this report, we have used the halophytic Arabidopsis relative, E. salsugineum to identify biochemical alterations and dormancy-associated gene expression changes underlying the widespread phenomenon of salt-mediated inhibition of halophyte seed germination ( Ungar, 1978 ; Gulzar and Khan, 2001 ; Song et al, 2005 ; Qu et al, 2008 ; Orsini et al, 2010 ; Al-Hawija et al, 2012 ; Cao et al, 2012 ; Gul et al, 2013 ). It had been previously reported that E. salsugineum seed germination is inhibited by salt ( Inan et al, 2004 ; Orsini et al, 2010 ), and we further extended these findings to show that E. salsugineum seeds respond to as low as 50 mM NaCl, which causes a delay in germination ( Figure 1A ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, seeds in the seed bank can undergo seasonal cycling between physiologically dormant and non-dormant states ( Baskin and Baskin, 1998 ; Cadman et al, 2006 ; Footitt et al, 2011 ; Penfield and Springthorpe, 2012 ; Ibarra et al, 2015 ). One major environmental factor affecting germination of halophytes is the concentration of salt in the soil, and it has been known for decades that seeds of a large number of halophytes will not germinate on high levels of salt ( Ungar, 1978 ; Gulzar and Khan, 2001 ; Khan et al, 2003 ; Song et al, 2005 ; Qu et al, 2008 ; Orsini et al, 2010 ; Al-Hawija et al, 2012 ; Cao et al, 2012 , 2014 ; Gul et al, 2013 ). Although the reduction in seed germination rates and percentages of halophytes in response to salt has been well-documented, there has been no systematic investigation of the biochemical and gene expression changes occuring in halophytic seeds during salt-mediated inhibition of germination.…”
Section: Introductionmentioning
confidence: 99%
“…300‐mM NaCl) has been reported as 4°C–8°C for Armeria maritima (Al‐Hawija et al . ), 5°C–25°C for Atriplex prostrata and Salicornia europaea (Egan & Unger ), 10°C–20°C for Limonium cossonianum (Luque et al . ) and L. tabernense (Fernández et al .…”
Section: Resultsmentioning
confidence: 99%
“…), 20°C–32°C for Aster tripolium and Triglochin maritimum (Al‐Hawija et al . ), 25°C for Chloris virgata (Zhang et al . , ), 25°C–35°C for Salsola iberica (Khan et al .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, cold stratification has been widely used to break seed dormancy and enhance the germination percentage. In A. tripolium, the germination of seeds under cold treatment was obvious higher than that without stratification [20]. Also, Lohengrin et al [21] indicated that seed germination with stratification increased significantly.…”
Section: Discussionmentioning
confidence: 97%